Palamedes Swallowtail, Laurel Swallowtail, Papilio palamedes (Drury) (Insecta: Lepidoptera: Papilionidae) - Donald W. Hall (EDIS)
The palamedes swallowtail is a large, dark swallowtail butterfly marked with yellow spots and bands. It is particularly common in and near swampy woods. https://edis.ifas.ufl.edu/in217